Potensi Baruas Kelor dalam Mengatasi Masalah Stunting Balita Usia 12 - 23 Bulan di Wilayah Kerja Puskesmas Tampa Padang - Muh Hasyim; Najdah Najdah; Nurbaya Nurbaya (Jurnal Sehat Mandiri, 2023)
The prevalence of stunting in West Sulawesi has increased from 33.8% in 2021 to 35.0% in 2022. Meanwhile, based on e-PPGBM data, the highest prevalence of stunting was in the working area of the Tampa Padang Health Center, Mamuju, namely 47.3%. To overcome the problem of stunting, foods with nutritional value are needed, especially calcium, iron, zinc, and protein. Moringa leaves are a type of food that is rich in various nutrients. Adding moringa leaf flour to MP-ASI products is expected to improve the nutritional status of stunted children. The study aimed to determine the effect of giving moringa oil on improving the nutritional status of stunted toddlers by using a quasy experiment research method pre-test and post-test control group design. The sample was toddlers aged 12-23 months, as many as 23 people per group, 1 group was given the intervention of Moringa Baruas cake, and 1 group was given Baruas cake without Moringa (control). Analysis was performed using independent t-tests, paired t-tests and Ancova statistical tests. The study results showed an effect of giving Baruas cake to increase length, body weight, nutritional status (height-for-age, weight-for-height) and length in the intervention and control groups with a p-value <0.05. Giving segmented cakes has an effect on increasing weight, length, and nutritional status in toddlers. Giving Baruas cake is recommended to overcome the problem of stunting with more prolonged feeding.